Study of seasonal variations of some physico-chemical characteristics of sina kolegoan dam at Osmanabad district (M.S.) - Jadhav, Swati; Borde, Sunita; Jadhav, Dilip (International Multidisciplinary Research Journal, 2011)
The present study designed to demonstrate the seasonal variations in Physico-chemical parameters of Sina kolegoan Dam from June 2009 to May 2010. Water samples were collected monthly basis and analyzed for estimation of water temperature, pH, Dissolved oxygen, free CO2, total alkalinity. The overall water quality of the study sites remained within the safe limits throughout the study period. An attempt has been made to explain the effect of seasonal changes on Physico-chemical characteristics of Sina kolegoan Dam.Â